Dark Triad and Tendency to Misuse Assets: An Empirical Study - Farisa, Sifa; Chariri, Anis (E-Jurnal Akuntansi; Vol 35 No 4 (2025), 2025)
This study aims to investigate the influence of dark triad personality traits (Machiavellianism, narcissism, and psychopathy) on tendency to commit asset misappropriation This study uses quantitative method, with questionnaire as data collection instrument. The sample of this study consists of 124 civil servants in head office of National Civil Service Agency. Using partial least square with WarpPLS 7.0 to test the hypothesis, the result shows that Machiavellianism and psychopathy have positive effect on the tendency to misuse assets. Meanwhile, narcissism has no effect on the tendency to misuse assets. This study contributes to forensic accounting literature by highlighting the importance of examining psychological factors, like traits in dark triad, when investigating fraud especially asset misappropriation schemes. Keywords: Dark triad; Misuse Asset; Machiavellianism; Psychopathy; Fraud.